Contribución de los genes chr en la resistencia a cromato de Burkholderia xenovorans LB400 - Reyes Gallegos, Rosa Isela (Universidad Michoacana de San Nicolás de Hidalgo, 2015)
CHRA is a hydrophobic protein that expels chromate dependently membrane potential. CHRA bacterial homologous are grouped within the CHR chromate transporter superfamily. They are classified according to their size in single-domain proteins or SCHR (200 aa) and bidominio proteins or LCHR (400 aa). Burkholderia xenovorans LB400, chromate-resistant bacteria, has 9,043 genes distributed in three replicons: Chromosome 1, Chromosome 2 and megaplasmid. Its genome has chr genes encoding four proteins LCHR and two pairs SCHR. Chr genes cloned and transferred into Escherichia coli conferred chromate resistance, depending on culture conditions, suggesting that the expression of chr genes is regulated by sulfate. Analysis by RT-qPCR of chr genes in LB400 showed that are differentially expressed and that sulfate does not regulate their expression. The chrA2 gene encoded in the megaplasmid, this chr gene was the only whose expression was induced by chromate suggesting that is the most important for resistance chromate phenotype of LB400. The objective of this study was to determine the chr genes involvement in resistance chromate B. xenovorans LB400. First susceptibility chromate group B. xenovoras strains was determined selecting the CAC-124 strain, highly sensitive chromate as recipient of chr genes. Transferring each chr genes showed that the genes of adaptive replicons (chrA1b and chr1NCb, chromosome 2 and chrA2, the megaplasmid) conferred a higher level of resistance that chromate central chromosome chr genes (chrA1a, chrA6 and chr1NCa), the chrA2 gene that conferred the highest level of resistance.

ChrA es una proteína hidrofóbica que expulsa cromato de forma dependiente del potencial de membrana. Homólogos bacterianos de ChrA se agrupan dentro de la superfamilia CHR de transportadores de cromato. Se clasifican de acuerdo a su tamaño en proteínas monodominio o SCHR (200 aa) y proteínas bidominio o LCHR (400 aa). Burkholderia xenovorans LB400, una bacteria resistente a cromato, posee 9,043 genes distribuidos en tres replicones: Cromosoma 1, Cromosoma 2 y Megaplásmido. Su genoma posee genes chr que codifican cuatro proteínas LCHR y dos parejas SCHR. Los genes chr clonados y transferidos a Escherichia coli confirieron resistencia a cromato, dependiendo de las condiciones del cultivo, sugiriendo que la expresión de los genes chr es regulada por sulfato. El análisis por RT-qPCR de los genes chr en LB400 mostró que se expresan diferencialmente y que el sulfato no regula su expresión. El gen chrA2, codificado en el megaplásmido, fue el único gen chr cuya expresión fue inducida por cromato sugiriendo que éste es el más importante para el fenotipo de resistencia a cromato de LB400. El objetivo de este trabajo fue determinar la participación de los genes chr en la resistencia a cromato de B. xenovorans LB400. Primeramente se determinó la susceptibilidad a cromato de un grupo de cepas de B. xenovoras, seleccionando a la cepa CAC-124, altamente sensible a cromato, como receptora de los genes chr. La transferencia de cada uno de los genes chr mostró que los genes de los replicones adaptativos (chr A1b y chr1NCb, del cromosoma 2 y chrA2, del megaplásmido) confieren un mayor nivel de resistencia a cromato que los genes chr del cromosoma central (chrA1a, chrA6 y chr1NCa), siendo el gen chrA2 el que confirió el mayor nivel de resistencia.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2015-2240; Megaplásmido; Adaptativos; Transformantes; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3924